Regional Differences in Adult Body Height in Kosovo - Bojan Masanovic; Tonci Bavcevic; Ivan Prskalo (Montenegrin Sports Academy, 2019)
Th is study aimed to test average body heights in both the male and females of Kosovo, as well as the diff erences in heights of both sexes in relation to the Kosovo administrative regions. A total of 1623 subjects participated in the research: 830 boys and 793 girls all attending their fi nal year of secondary school. Th e anthropometric measurements were taken for subjects of both sexes from fi ve diff erent administrative regions of Kosovo. Th e measurements of body heights were taken by trained measurers in conformity with the ISAK protocol. Means and standard deviations were calculated for ages and body heights, as were frequencies for the calculation of the density of very short and very tall subjects. Th e results indicated that the average height of the male population of Kosovo was 179.52±5.96 centimetres and of the female population 165.72±4.93 centimetres. Th ese results classify both the male and female populations of Kosovo among the tallest in the world. Regarding the regional diff erences, some variations have been observed, and the diff erences in body heights among specifi c regions clearly confi rm the assumption that the population living in the Dinaric Alps is taller in relation to the rest of the population, while the specifi c average height of the central region, where the capital city is located, refl ects the expected situation conditioned by continuous migrations from all other parts of Kosovo, as well as the fact that there is a growing secular trend towards the territory of the capital city, due to better economic and living conditions.